PENGARUH JENIS PUPUK ORGANIK DAN PORPOSI PUPUK ANORGANIK TERHADAP KARAKTER FISIOLOGI DAN SERAPAN HARA N TANAMAN PADI SAWAH - Purwanto Purwanto; Utomo Utomo; Bambang Rudianto Wijonarko; Budi Supono Indaryanto (Universitas Tadulako, 2011)
The aim of this research was to determine the effect of inorganic fertilizer proportion and organic fertilizer as well as its interaction to N uptake, N uptake efficiency, and physiological characters of rice plant. This research was conducted in the Experimental Farm of Agriculture Faculty of Jenderal Soedirman University Purwokerto, with soil type used was Inceptisol and located 110 m above sea level. This research was arranged using split plot design with four replicates. The main plots were the type of organic fertilizers i.e cow manure 5 t/ha, and straw compost 5 t/ha. The subplots were the proportion of inorganic fertilizers i.e P1: general dose recommendation (250 kg Urea, 150 kg SP-36 and 150 kg KCL), P2: 75% of general dose recommendation (187.5 kg Urea, 112.5 kg SP-36 and 112.5 kg KCL), P3: 50% of general dose recommendation (125 kg Urea, 75 kg SP-36 and 75 kg KCL), P4: P and K according to soil nutrient status + N according to Leaf Color Chart scale (LCC), P5: 150 kg SP-36, 150 kg KCl, and N according to LCC scale, and control (without fertilizer). The observed variables were leaf area index, leaf greenness, leaf chlorophyll content, N uptake, and N uptake efficiency. Data was analyzed using F test and if the differences were significant, the analysis was proceed with DMRT test at 5% error levels and orthogonal contrast test. The results showed that the dose of inorganic fertilizer increased the leaf area index, chlorophyll content, N uptake and N uptake efficiency. The reduction of inorganic fertilizer dose up to 50% of general dose increased the content of chlorophyll a. N uptake efficiency was higher in the N fertilizer added based on LCC and P and K based on soil nutrient status treatment than the recommendation dose when straw compost was applied.